العمران المستدام فی ظل التحول الرقمی والثورة المعلوماتیة - نادین عبد الفتاح (Journal of Engineering Research - Egypt, 2020)
فرضت الوسائل والتطبیقات التکنولوجیة مجموعة منالتحولات الرقمیة العالمیة والاقلیمیة على تخطیط عمران المدن فیماعرف بالثورة الرقمیة العمرانیة، التى انعکست بدورها على جمیعملامح العمران للمدن من توزیع استعمالات اراضى حتى التشکیلالعمرانى للمبانى. فأدى التطور التکنولوجی السریع للقرن الواحدوالعشرین فی مجال العمران إلى إنتاج نموذج جدید من العمران یعرفباسم العمران المستدام القائم على الابتکار والابداع باستخدام أحدثالوسائل والتطبیقات التکنولوجیة للوصول الى جودة الحیاة بالمدینة التیاطلق علیها المدینة الذکیة المستدامة Smart Sustainable City ،وذلک من خلال دعم قدرتها وفاعلیة نظمها وتسهیل الحصول علىالخدمات العامة، ودعم التنافسیة العالمیة، ودفع عملیة التحدیث، بحیثیمکن القول إن هذا النوع من المدن ینقل الثقل الاقتصادی للمدن العملاقةویدعم مکانة الدولة وصورتها العمرانیة.وفى ظل التعرف على مفاهیم التحولات الرقمیة السریعة للمدنالاجنبیة والعربیة الأکثر تطوراً فی مجال التکنولوجیا والأکثر قدرةعلى الإبداع، اصبحت المدن الذکیة هدف من اهداف الدول لتنمیةمجتمعاتها العمرانیة کی تصبح مستدامة. ومن هذا المنطلق بات التحولنحو المدینة الذکیة المستدامة یمثل الحل الأمثل للتغلب على التحدیاتوالسلبیات والمشاکل المصاحبة للنمو السریع الغیر منضبط للمدن، ویتمهذا التحول بإحدى طریقین او بالاثنین معا، الطریق الاول هو بذلالجهود من اجل تحویل المدن القائمة بالفعل او قطاعات منها إلىمجتمعات متصلة ذکیة مستدامة صدیقة للبیئة ولهذا الطریق وسائلهوالیاته التى تتوقف على الظروف المحلیة المتشابکة، اما الطریق الثانىهو انشاء مدن ذکیة مستدامة جدیدة تحقق اهداف اقامة مجتمعاتمتکاملة على اسس عصریة متطورة تتجنب کل سلبیات ومشاکل المدنالقدیمة، وفى نفس الوقت تجذب قطاعات من المواطنین لترک المدنالقدیمة والاقامة فى المدن المستجدة وبذلک یتم تخفیف بعض الضغوطعن المدن القدیمة. وتنتهج اغلب الدول الطریقین فى نفس الوقت بحیثیتم انشاء مدن جدیدة مثل العاصمة الاداریة الجدیدة بمصر ومدینةسونغدو بکوریا، کما تم ذلک جنبا الى جنب مع تطویر المدن القدیمة اوقطاعات منها مثل مدینة دبی بالإمارات. Technological applications and tools have imposed a set of global and regional digital transformation on the urban planning of the cities, known as digital urban revolution, which reflected on all features of urbanization such as the land use distribution to the shape of buildings. The rapid development of the 21st century’s technology in the Urban Planning field, led to theproduction of a new model of cities known as Sustainable Urbanization, which is based on innovation and creativity using the latest technological tools and applications in order to achieve the good quality of life in the city, via supporting its capacity and system, and facilitating access to public services, and pushing the process of modernization. Therefore, we can say that this type of cities transfers the economic planetary cities and the giant demographic cities to another kind of international cities that supports the state and its urban image. These cities called Smart Sustainable City. This model of cities is the subject of future competition between the countries that are more creative and more developed in technology.Under the light of the quick digital transformation of foreign and Arab cities that are more advanced in the field of technology, smart cities have become one of the goals to develop sustainable urban societies. It was agreed to build the proposed entrance to deal with smart cities using multi-dimensional urban models for spatial analyzes of the city elements. From this standpoint, the shift towards a sustainable smart city has become the best solution to overcome the challenges and problems associated with the quick uncontrollable growth of cities. This transformation takes place in two ways: the first way is to make efforts to convert the existed cities to smart, sustainable, environmentally friendly and connected communities; this pathway has its own means and mechanisms that depend on the interlocking local conditions. The second way is the establishment of new smart sustainable cities that achieve the goals of establishing integrated societies based on modern development avoiding all the old cities problems and negativity, and at the same time attracting sectors of citizens in order to leave the old cities and live in the new smart cities, thus relieved some of the pressure in the old cities. Most countries follow the two paths at the same time, so these new cities such as thenew administrative capital of Egypt and Songdo city in Korea, will be established, as what was done alongside the development of old cities or sectors like Dubai in United Arab Emirates.